واقع غرف مصادر التعلم في المدارس الدامجة للتعليم الأساسي: دراسة ميدانية من وجهة نظر معلميها ومديري مدارس الحلقة الأولى في مدينة اللاذقية - زمرد، أميرة; علي، خضر; عيريق، نجله حسين (جامعة تشرين, 2021)
هدف البحث الحالي إلى رصد واقع غرف مصادر التعلم في المدارس الدامجة للتعليم الأساسي (حلقة أولى) في مدينة اللاذقية من حيث: (المبنى والتجهيزات، المنهاج وسير البرنامج الدراسي المتبع فيها، كفاية معلميها) وذلك من وجهة نظر مديري المدارس الدامجة ومعلمي غرف المصادر، كما هدف إلى تحديد الصعوبات التي تعيق عمل المعلمين فيها وتقديم مقترحات لمواجهة الصعوبات. اعتمدت الباحثة المنهج الوصفي، واستخدمت بطاقة رصد لواقع غرف مصادر التعلم في المدارس الدامجة للتعليم الأساسي (الحلقة الأولى) في مدينة اللاذقية، تضمنت بطاقة الرصد: الشروط المتوافرة في الغرفة من حيث البيئة المادية، ودرجة توافر التجهيزات المتعلقة بالأثاث والأجهزة والمصادر التعليمية فيها، ودرجة كفايتها، كما استخدمت المقابلة التي تم إجراءها على عينة مؤلفة من (5) من مديري المدارس الدامجة و (10) من معلمات غرفة مصادر التعلم في المدارس الدامجة والبالغ عددهم خمس مدارس في مدينة اللاذقية. أظهرت نتائج البحث أن من أكثر شروط البيئة المادية المتوافرة في غرفة المصادر الآتي: سهولة الوصول إليها، موقعها في الطابق الأرضي، ووجودها ضمن مبنى المدرسة، أما فيما يتعلق بكفاية مساحة غرفة المصادر وبعدها عن الضوضاء متوافرة بدرجة متوسطة، واتفقت نتائج بطاقة الرصد هنا مع نتائج المقابلة التي أجرتها الباحثة مع أفراد العينة، كما أظهرت النتائج أن التجهيزات في غرفة المصادر غير متوافرة وغير كافية، وتبين من خلال المقابلة أنه لا يوجد منهاج محدد في غرفة المصادر إنما هناك خطة فردية بحسب نوع الاعاقة وشدته، يتم وضع الخطة بناء على نتائج الاختبارات والمقاييس، وأن من أهم المهارات التي يجب أن تتوافر لدى معلمي غرف المصادر خضوعهم لدورات تدريبية وأن يمتلكوا صفات شخصية تؤهلهم للعمل فيها، وكانت من أهم الصعوبات التي أشار إليه أفراد العينة نقص الأثاث والأجهزة والمصادر التعليمية وقلة الحوافز المادية والمعنوية لمعلمي غرف المصادر، وكان من أهم المقترحات للحد من الصعوبات توفير النواقص والحوافز المادية والمعنوية.
The current research aimed to monitor the reality of learning resource rooms in inclusive schools of basic education in Lattakia City, in terms of: (building and equipment, curriculum and adopted course of study, efficiency of teachers, and difficulties that hinder their work and efforts) from the standpoint of the principals of integrated school and the teachers of resource rooms. In addition, the research seeks to present suggestions to address difficulties. The researcher adopted the descriptive approach and used a card to monitor the reality of learning resource rooms in basic education schools (first cycle) in Lattakia. The monitoring card included: the conditions available in the room in terms of the physical environment, the extent of availability of furniture, equipment, and educational materials as well as their efficiency. The interview method was also used, performed on a sample of (5) principals of inclusive schools and (10) teachers of the learning resource rooms in five inclusive schools in Lattakia. Research results showed that: the most available requirements of the physical environment in the resource room included (easy accessibility, ground-floor location, and existence within the school building). The percentage of Yes-answers was (100%). However, heating was insufficient, with (100%) of No-answers. As for the efficiency of the resource room space and being away from noise, the percentage of responses was (60%) of No- answers. The results of the monitoring card here were consistent with the results of researcher's interview with the members of the sample. The results also showed that the equipment in the resource room is neither available nor sufficient. Moreover, through the interview, it was found that there was no specific curriculum in the resource room. Instead, there was an individual plan according to the type and severity of the disability. That plan was developed based on test results and standards. Furthermore, one of the most important skills that resource room teachers must own is to take training courses and to have personal qualities that qualify them to work in such rooms. Among the most significant difficulties cited by the sample members were the lack of furniture, equipment and educational resources and the lack of moral and material incentives for teachers of resource rooms. Accordingly, one of the most important suggestions to resolve difficulties was the provision of deficiencies as well as moral and material incentives.
Keywords: التعليم الأساسى -- غرف مصادر التعلم -- مدارس الدمج -- ذوو الاحتياجات الخاصة -- سوريا